Reventive Maintenance Jaringan Fiber To The X (FTTX) Di PT Moratelindo Tbk - Muhamad Burhanudin; Siswo Wardoyo (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The importance of maintenance on the FTTX network as a communication service infrastructure is to avoid interference. Good maintenance activities must be carried out in an appropriate and consistent manner. The research methods used are observation, interviews with related parties as well as documentation and literature study. The maintenance activities carried out consist of FO Cut, FAT Loss/Problem, Bad Core, Low RSL, Bed Barrel, Bed Pigtail, FO Bending. Fiber To The X (FTTX) will be carried out periodic maintenance according to a predetermined schedule if a disturbance is found then there must be more action. Translated with DeepL.com (free version)